ChemInform Abstract: Enantioselective Organocatalyzed Oxa‐Michael‐Aldol Cascade Reactions: Construction of Chiral 4H‐Chromenes with a Trifluoromethylated Tetrasubstituted Carbon Stereocenter. Issue 30 (July 2015) - Zhang, Jing; Ajitha, Manjaly J.; He, Lin; Liu, Kai; Dai, Bin; Huang, Kuo‐Wei
Abstract 4H‐Chromenes bearing a trifluoromethylated chiral quaternary carbon center are synthesized via a novel oxa‐Michael—aldol cascade reaction between 2‐trifluoroacetylphenols and alkynals.